The Traditional Approaches for the Management of Mental Diseases W.S.R. to Indigenous Herbs in Manovikara - Vaidya, Chaitanya H. (Journal of Drug Delivery and Therapeutics, 2018)
The uses of ayurveda not only reside around as main stream of ancient science but it also served as complementary or alternate medicine. Ayurveda provides principles to maintain good healthy status of mind, body and soul. Ayurveda also offer therapies for the management of mental health issues including; shodhna therapy, use of herbs & formulation and yoga therapy. The use of indigenous herbs & plants greatly recommended by ancient acharya in mental illness such as; Bacopa monnieri, Centella asiatica, Amla, Mucuna, Zizyphus jujube, Kava and Saffron. This article describe role of indigenous herbs and traditional medicine in the management of mental problems.Keywords: Ayurveda, Mental Health, Kaya-Chikitsa, Indigenous Herbs and Swasthya.